Improving Students' Descriptive Writing Achievements Through The Mind Mapping Method - Carolina, Carolina; Susanti, Susanti; Lestari, Febrika Dwi; Simanjuntak, Abdi Putra Arianto (Jurnal Ilmu Sosial Mamangan, 2025)
This study focused on finding out the effect of using mind mapping method of   in teaching writing descriptive text. The objective of the study is to find out whether or not the mind mapping method affects students’ achievement in writing descriptive text. This study was conducted by applying study case research. The subject of the study was the Second-year students of HKBP Nommensen University. The writer took group A which consists of 20 students used Mind mapping. The writer took one class as random sampling to see the effect of Mind mapping method in teaching writing descriptive text. The data were taken by giving writing test. The tests were divided into two tests: pre-test and post-test for both the second cycle and the first cycles. The mean score of cycle I class is 57 and the post-test is 85,55. The mean score of pre-test in the cycle I is 53,4 and the post-test is 82,1. It is conducted that the mean score of cycle II is higher than a the first cycle. The result that the calculated > t-table as the level of significance p=0.05 (4,48 >1.734). The alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. It is suggested that teachers of English subject apply Mind mapping method   as an alternative teaching technique to help writing ability at tenth grade students in university level.